66.6k views
1 vote
If h(x)=6-x what is the value of (hxh)(10)?

User Shoba
by
4.6k points

2 Answers

4 votes

Answer:

16

Explanation:

h(x) × h(x) = (6 - x)²

(h × h)(10) = (6 - 10)² = (- 4)² = 16

User Robinmag
by
5.6k points
5 votes

For this case we have by definition, that given two functions, then:


(f * g) (x) = f (x) + g (x)

Here, we want to find (
(h * h) (x):


(h * h) (x) = (6-x) (6-x)\\(h * h) (x) = 36-6x-6x + x ^ 2\\(h * h) (x) = 36-12x + x ^ 2

We want to find the value of the function when
x = 10.


(h * h) (10) = 36-12 (10) + (10) ^ 2\\(h * h) (10) = 36-120 + 100\\(h * h) (x) = 16

Answer:


(h * h) (x) = 16

User Beavel
by
5.3k points